THE ROLE OF DIGITAL MARKETING IN INCREASING THE NUMBER OF TOURISTS IN TOURIST DESTINATIONS - Rusti Mawa Praci; Yuliana Yuliana (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2026)
Digital marketing has grown rapidly in recent years and has become one of the main tools for the tourism sector to attract tourists. Many tourist destinations are now utilizing various digital platforms, such as social media, websites, and digital advertising to promote their products and services. Digital marketing allows for broader, more affordable, and more targeted promotions to specific audiences, which can increase the number of tourist visits. However, despite the many studies that have been conducted on digital marketing, there is still a need for a deeper understanding of its impact on increasing tourist numbers, both in local and international contexts. Therefore, a systematic review through the Systematic Literature Review (SLR) is needed to explore and analyze findings related to the influence of digital marketing on tourists' decisions in choosing tourist destinations.